Toxicological Evaluation of Leucaena leucocephala (Subabul) Gum - Soni, P. L.; Dikshith, T. S. S.; Raizada, R. B. (Indian Forester, 1986)
Acute toxicity of Su-babul gum was determined by the oral as well as intraperitoneal administration to male and female rats and mice. The oral administraion dose at the level of 4 and 8g/kg body weight could not trigger any signs of toxicity or death. Injecting the gum (upto 1000 mg/kg) intraperitonealy in mice, indicated that it is non toxic and is devoid of any significant pharmacological activity. One can envisage no toxicity problem due to this material.